The behaviour of wintering Smew in southern Sweden - Nilsson, Leif (Wildfowl, 1974)
The general, feeding, agonistic and sexual behaviour of wintering Smew Mergus albellus in southern Sweden is described, together with related aspects of habitat selection and sex ratios.